Mutations of CX46/CX50 and Cataract Development - Shi, Yumeng; Li, Xinbo; Yang, Jin (Frontiers in Molecular Biosciences, 2022)
Abstract: Cataract is a common disease is aging population. Gap junction has been considered a central component in maintaining homeostasis for preventing cataract formation. Gap junction channels consist of connexin proteins with more than 20 members. Three genes including GJA1, GJA3, and GJA8, that encode protein Cx43 (connexin43), Cx46 (connexin46), and Cx50 (connexin50), respectively, have been identified in human and rodent lens. Cx46 together with Cx50 have been detected in lens fiber cells with high expression, whereas Cx43 is mainly expressed in lens epithelial cells. Disrupted expression of the two connexin proteins Cx46 and Cx50 is directly related to the development of severe cataracts in humans and in mice. In this review article, we describe the main role of CX46 and CX50 connexin proteins in the lens and the relationship between mutations of CX46 or CX50 and hereditary cataracts. Furthermore, the latest progress in the fundamental research of lens connexin and the mechanism of cataract formation caused by lens connexin dysfunction are summarized. Overall, targeting connexin could be a novel approach for the treatment of cataract.